1985
DOI: 10.1037/0022-3514.48.6.1490
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of self-esteem: Refining our methods.

Abstract: Abstract:A review of the literature indicates that (a) very little attention has been devoted to measurement problems plaguing the study of self-esteem and (b) few studies employ more than one type of self-esteem instrument. This study addresses these issues by using eight measures of self-esteem involving self-reports, ratings by others, and a projective instrument. Their intercorrelations are examined to provide preliminary validational evidence; then, confirmatory factor analysis is used to construct measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
189
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(197 citation statements)
references
References 47 publications
8
189
0
Order By: Relevance
“…Item scores are summed, and higher scores are indicative of higher self-esteem. Validity of the scale is supported by a significant positive correlation with peer ratings of self-esteem (Demo, 1985), and, in a review of the convergent and discriminant validity of the Rosenberg Self-Esteem Inventory, Byrne (1983) concluded that this measure was one of the most valid measures of global self-esteem. Wylie (1989) reported a satisfactory 7-month test-retest correlation of r = .73 in high school students and a 2-week test-retest reliability of r = .85 in college students.…”
Section: Methodsmentioning
confidence: 97%
“…Item scores are summed, and higher scores are indicative of higher self-esteem. Validity of the scale is supported by a significant positive correlation with peer ratings of self-esteem (Demo, 1985), and, in a review of the convergent and discriminant validity of the Rosenberg Self-Esteem Inventory, Byrne (1983) concluded that this measure was one of the most valid measures of global self-esteem. Wylie (1989) reported a satisfactory 7-month test-retest correlation of r = .73 in high school students and a 2-week test-retest reliability of r = .85 in college students.…”
Section: Methodsmentioning
confidence: 97%
“…Also, respondents might pur posefully distort their answers for social-desirability or im age-management reasons. Distortions are especially likely when an accurate response is seen as either violating social norms such as politeness or prejudice (Demo, 1985;Dovidio & Fazio, 1992), jeopardizing one's self-image (Dovidio & Fazio;Gaertner & Dovidio, 1986;Sirgy, 1982), or going against the stereotypical answer (Haire, 1950). In short, no explicit measure can truly avoid the influence of respondents' control.…”
Section: Explicit and Implicit Measures In Consumer Research Explicitmentioning
confidence: 99%
“…Our discussion has focused particular attention on self-esteem and feelings of being in control. There is similarly strong evidence that investigators can confidently measure a person's global self-esteem using Rosenberg's Self-Esteem Scale (Fleming and Courtney, 1984;Reynolds, 1988;Demo, 1985) and a person's feeling of being in control using a subset of questions from Rotter's original Internal-External Locus of Control Scale (Lefcourt, 1991). For a more complete discussion of issues relating to the using the Rosenberg and Rotter scales in economic research, the interested reader should begin with Goldsmith, Veum and Darity (1995c).…”
Section: Quantifying the Connection Between Unemployment And Emotionamentioning
confidence: 99%
“…Another aspect of convergent validity is that the results of self-reporting by individuals should correspond to observations by peers or trained observers. Demo (1985) compared these different measures.…”
Section: Quantifying the Connection Between Unemployment And Emotionamentioning
confidence: 99%